Save more tomorrow : practical behavioral finance solutions to improve 401K plans - Benartzi, Shlomo; Lewin, Roger (New York : Portfolio/Penguin, 2012)
The book provides all the secrets to making a retirement plan work.
Acknowledgments -- Introduction -- Save -- Auto-takeoff -- Match optimizer -- The face tool -- Save more -- Save more tomorrow : 1.0 -- Save more tomorrow : 2.0 -- Imagine exercise -- Save smarter -- Investment solutions pyramid -- Lifetime statement -- Tangible account statement -- Overview -- The plansuccess behavioral audit -- Concluding remarks, and the way forward -- Appendix 1: Retirement savings questionnaire -- Appendix 2: Plan success behavioral audit questions -- Index.
Includes bibliographical references and index.
rua 29/04/13
Loans
Keywords: Finance, Personal -- Psychological aspects; Pension trusts -- Investments; Individual retirement accounts